Pemanfaatan Lahan Green House dengan Penanaman Bawang Merah sebagai Media Pembelajaran Panen Bawang Merah di Desa Purworejo - Mukhammad Nizar; Anastasia Ayu Anindya (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Purworejo Village, Ngantang District, Malang Regency is one of the onion producers in East Java. Purworejo Village has geographical and climatic conditions that support the growth of onions well. Fertile soil and sufficient rainfall enable farmers to obtain optimal harvest results. Agricultural knowledge and traditions that have been passed down from generation to generation have become valuable capital for local farmers in managing shallot crops well. In Purworejo Village there is agricultural land that uses a greenhouse system, however the green house has been unused and neglected because it is poorly maintained. The PPK HMD Management team is working together with the Karya Bakti 1 Farmers Group in Purworejo Village to revitalize and reuse greenhouse agricultural land for planting shallots. Methods used in revitalization include evaluating land conditions, soil analysis and fertilization, water management, and routine maintenance. The results of the revitalization of the greenhouse will be used as an outdoor education center which is useful for providing experience in raising shallots through to the harvesting process as an application of shallot farming theory.